Fostering sustainable food consumption: a theoretical framework for upcycled foods - Zhang, Xi-Yu; Chao, Ching-Tzu; Chen, Han-Shen (Frontiers in Psychology, 2025)
PurposeThis study investigates the psychological, social, and environmental determinants of consumers' purchasing intentions for upcycled foods by integrating Value-Belief-Norm Theory (VBNT), Social Cognitive Theory (SCT), and Self-Determination Theory (SDT) into a multi-theoretical framework.Design/methodology/approachA survey of 402 online respondents was conducted using convenience sampling, and partial least squares structural equation modeling (PLS-SEM) was used to analyze the results.FindingsThis study found that biospheric and altruistic values drive purchase intentions, enhancing consumers' sense of responsibility and the environmental and social benefits of upcycled food. Consequence awareness was identified as a critical mediator bridging consumers' values and attitudes toward upcycled food consumption. Social media advertising has been found to be a powerful external stimulus that strengthens consumers' self-efficacy, value identification, autonomy, and control motivation.OriginalityThis study contributes to the literature on sustainable consumption by demonstrating a multitheoretical approach to unravel consumer decision-making processes.Research limitations/implicationsThis study was based solely on a Taiwanese sample, where cultural characteristics (e.g., collectivism and the dominance of the Line app) may limit the generalizability of the findings, highlighting the need for cross-cultural research in this area. This study underscores the importance of strategies that align with values, enhance self-efficacy, and leverage social norms.Practical implicationsThe results of this study have practical implications for policymakers, marketers, and industry practitioners, who should develop strategies that emphasize the environmental and social benefits of upcycled foods while addressing consumers' motivational needs for autonomy and efficacy.Social implicationsThis study provides insights into fostering sustainable food consumption at the intersection of individual values, social norms, and marketing-driven stimuli.